This action might not be possible to undo. Are you sure you want to continue?

the s quare of the first by the second, plus three times the first by the square of th e second, plus the cube of the second. (a + b)3 = a3 + 3 · a2 · b + 3 · a · b2 + b3 (x + 3)3 = x 3 + 3 · x2 · 3 + 3 · x· 32 + 33 = = x 3 + 9x2 + 27x + 27 Cube Difference A cubed binomial (difference) is equal to the cube of the first, minus three tim es the square of the first by the second, plus three times the first by the squa re of the second, minus the cube of the second. (a - b)3 = a3 - 3 · a2 · b + 3 · a · b2 - b3 (2x - 3)3 = (2x)3 - 3 · (2x)2 ·3 + 3 · 2x· 32 - 33 = = 8x 3 - 36 x2 + 54 x - 27 Examples 1(x + 2)3 = x3 + 3 · x2 · 2 + 3 · x · 22 + 23 = = x3 + 6x2 + 12x + 8 2(3x - 2)3 = (3x)3 - 3 · (3x)2 · 2 + 3 · 3x · 22 - 23 = = 27x 3 - 54x2 + 36x - 8 3(2x + 5)3 = (2x)3 + 3 · (2x)2 ·5 + 3 · 2x · 52 + 53 = = 8x3 + 60 x2 + 150 x + 125 1. Monomial by Polynomial Example a.) b(ab+b²+1+x) = ab²+b³+b+bx ->distribute b to each of the terms in the pare ntheses. b.) 3x²(y+y²+2z-zyx) = 3x²y+3x²y²+6x²z-3x³zy

2. Square of Binomials Steps: (shortcut) Example a.) (x+y)² = (x)² + (x)(y)(2) + (y)² = x²+2xy+y² First, square the first term (x). Second, multiply the first term (x) , the last term (y) and the exponent (2), since it is in the second power. Last, square th e last term (y). By following the steps, it gives us x² +2xy+y² as our final answer.

2x. we should proceed now to step two. 3.b.(4)² = 9m^4 . the first term in the second parentheses. Therefor the final answer is 2x^4 . To ge t the sum. b.16 c.5x² .) (b+c)(b-c) = (b)² . s0 2^2 means (2)² = 4.) (a²-4)² = (a²)² + (a²)(-4)(2) + (-4)² = a^4-8a² +16 NOTE: This rule is only applicable on the square of binomials. 2x² & x². Second. the final answer is b² -c² . only that the sign should be oppo . Second. Lastly. we should see to it that the terms in the second parentheses coincides wi th the first. and the inner terms 1 & x² = x². we will get the sum of the outer terms.3. check if the second term in the second parentheses. That is. To check. b. should be t he product if we square the first term in the first parentheses. c & d are constants.) (4x-7y)(4x+7y) = (4x)² . Steps: (shortcut) Example a. 2x² & -3 = -6x².(7y)² = 16x² .(c)² = b² . 2x & -1. x²-6x² = -5x². b. we can use a^ to show an exponent.) (3m² -4)(3m² +4) = (3m²)² . we are to square the first term (b) and the second term (c).49y² 4. If the answer is correct.) Sum and Difference of Cubes Steps: (shortcut) Example a.) (5x-7)(8x-1) = 40x² + (-5x) + (-56x) + 7 = 40x² -61x + 7 5. we would have to delete -bc and bc (in the process) because the answer is 0.3 We can come up with the answers mentally by using the FOIL method. is the product o f the terms in the first parentheses.) (3x-5)(4x+3) = 12x² + 9x + (-20x) + (-15) = 12x² -11x -15 c.1 First.c² If the given terms (values) are the same but they have opposite signs in between .) (2x²+1)(x²-3) = 2x^4 + (-6x ²) + x² + (-3) = 2x^4 . The product is 2x^4. Using the FOIL method. 2x. In some of the ex amples. th e produuct is -3. we wil l get the product of the first terms.) (2x-1)(4x²+2x+1) = (2x)³ + (-1)³ = 8x³ . 4x². Binomials of the form (ax+b)(cx+d) where a. First. (2 x)² = 4x². we will get the product of the last terms 1 & -3. Sum and Difference of Binomials Steps: (shortcut) Example a. Then we will use the negative sign in between.) (2x+5y)² = (2x)² + (2x)(5y)(2) + (5y)² = 4x²+20xy+25y² c. Therefore.5x² .

-1. Written as. b. Written as. If the second parent heses coincides with the first by following the steps given previously.6xz . we now have x² + 4y² + 9z² + 4xy . (-1)³ = -1. the second term. x.) (-3x+y-5z)² = (-3x)² + (y)² + (-5z)² + (-3x)(y)(2) + (-3x)(-5z)(2) + (y)(-5z)(2) = 9 x² + y² + 25z² -6xy + 30xz . (-3z)² = 9z² . the third term. check if the last term in the second parentheses. Therefore.) (-x-2xy-5y)² = (-x)² + (-2xy)² + (-5y)² + (-x)(-2xy)(2) + (-x)(-5y)(2) + (-2xy)(-5y) (2) = x² + 4x²y² + 25y² + 4x²y + 10xy + 20xy² Exercises: . 2y. the final answer is 8x³ .1 NOTE: We can follow the first to the third step mentally. -3z. Third. the third term.) (x² -2y)(x^4+2x²y+4y²) = (x²)³ + (-2y)³ = x^6 . Third.we can now give the final answer by finding the cube root of the first pa rentheses (2x-1).10yz c. x. (-1)² = 1. (2y)(-3z)(2) = -12yz Combining all the answers.) The Square of a Trinomial Steps: (shortcut) Example a. 1. Written as. (x)(-3z)(2) = -6xz Lastly. That is. we should get the product of the first term.6xz . and the exponent 2. and the exponent 2. a nd the exponent 2.) (x+2y-3z)² = (x)² + (2y)²+ (-3z)² + (x)(2y)(2) + (x)(-3z)(2) + (2y)(-3z)(2) = x² + 4y² + 9z² + 4xy . we should square the first term. we can n ow proceed to the last step. we should get the product of the first term. 2y. (x)(2y)(2) = 4xy. -3z. If the answer is correct. 3z. (2x)³ = 8x³ . (2y)² = 4y² . b.12yz .12yz First.-8y^3 6. 2y. Second. That is. and the third te rm.) (y+2)(y²-2y+4) = (y)³ + (2)³ = y³ + 8 c. and the second term. Lastly. Written as. x. we should get the product of the second term.site. is the square of the first term in the first parentheses. we should proceed to step three. (2x)(-1) = -2x -> 2x. (x)² = x² .

asdasda

asdasda

- Algebra Markscheme
- Institutiones Calculi DifferentialisEuler-Maclaurin
- tcs placement paper.docx
- lec13
- Mathematics S P1P2 Answer Schema_Pahang
- chp 13 notes 13.4-13.7 MM
- Introduction to Algorithm Design.chapter 1 Skiena
- Price PhD c3
- Convolutions
- Algebraic Expressions
- Bellman Ford 4up
- Practice Test 02-Mathematical Aptitude
- OLS Hardcode
- Programming in Mathematica
- 1.2.MathematicalBackground
- Identities for Number Series and Their Reciprocals Dirac Delta Function Approach
- Warranty Cost Paper9_Jun
- Modern Algebra Final
- Functions
- APDISE1Lecture6 Sequences
- ECON1203 Finalexam Coverandtables 2014s2
- Relational Algebra
- mid[1]
- Bansal Sheet Solution
- 05_ECE MATH 311_Proofs Applications on Sets & Summation
- Solved Examples of Partial Differential Equations of Second Order
- communication Sheet solved problems
- (05) Kohn-Sham Equations for DFT
- notes-4
- Threshold Ing Review
- Katesilog.txt

Are you sure?

This action might not be possible to undo. Are you sure you want to continue?

We've moved you to where you read on your other device.

Get the full title to continue

Get the full title to continue reading from where you left off, or restart the preview.

scribd